My avatar moves with me, so I am the one acting: Avatar responsiveness supports implicit sense of agency in virtual reality - Marika Mariano; Giulia Stanco; Caterina Negrone; Niccolò Raffa; Massimo Montanaro; Emanuele Sapio; Nadia Bolognini; Alessandro Gabbiadini; Laura Zapparoli (PLoS ONE, 2026)
Virtual reality (VR) allows users to interact with computer-generated environments in a controlled yet immersive manner. One of its most relevant features is its ability to induce virtual embodiment, the process of becoming rooted in a virtual body. A key component of this experience is the sense of agency over the action-outcomes produced in the virtual environment. However, to date, no study has jointly examined explicit and implicit senses of agency within a VR paradigm in which actions lead to consequences occurring entirely in the virtual environment. To this aim, we conducted two consecutive experiments in 70 healthy adults, who performed active or passive hand movements to switch on a virtual lightbulb. On a trial-by-trial basis, explicit agency was assessed through self-reported ratings, and implicit agency through intentional binding across three action-outcome delays (200, 400, and 600 ms). In Experiment 1 ("still avatar", n = 35), participants performed the task observing stationary virtual hands. Because this setup did not elicit the typical intentional binding phenomenon, indicating no evidence of implicit agency under these conditions, we conducted Experiment 2 in an independent sample ("responsive avatar", n = 35), in which the avatar’s hands moved synchronously with participants’ real movements. Across both experiments, participants reported significantly greater explicit agency during active than during passive movements, regardless of avatar responsiveness. In contrast, intentional binding was observed only when the avatar’s movements mirrored the participant’s real movements (Experiment 2), and exclusively for the shortest action-outcome delay (200 ms). These findings suggest that avatar responsiveness is associated with the emergence of implicit, but not explicit, sense of agency. This dissociation advances our understanding of the mechanisms underlying agency in immersive environments and informs the design of VR-based neurorehabilitation interventions that promote a stronger sense of control.